2018
DOI: 10.1002/cbic.201800097
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crystallography and Site‐Direct Mutagenesis Analysis of the Poly(ethylene terephthalate) Hydrolase PETase from Ideonella sakaiensis

Abstract: Unlike traditional recycling strategies, biodegradation is a sustainable solution for disposing of poly(ethylene terephthalate) (PET) waste. PETase, a newly identified enzyme from Ideonella sakaiensis, has high efficiency and specificity towards PET and is, thus, a prominent candidate for PET degradation. On the basis of biochemical analysis, we propose that a wide substrate-binding pocket is critical for its excellent ability to hydrolyze crystallized PET. Structure-guided site-directed mutagenesis revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
188
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(202 citation statements)
references
References 24 publications
12
188
0
2
Order By: Relevance
“…The PETase-specific DS1, on the other hand, is located adjacent to the active site and connects the b7-a5 and b8-a6 loops that harbor the catalytic acid (D177) and catalytic base (H208), respectively (Fig. Interestingly, PET hydrolysis measured under reducing conditions and mutagenesis experiments indicate that DS1 depletion significantly reduces enzyme activity, suggesting that DS1 plays a critical role in PETase activity [9,[11][12][13]. In addition, the b8-a6 loop in PETase is three residues longer than that of other homologous enzymes (Fig.…”
Section: Unique Structural Features Of Petasementioning
confidence: 99%
See 2 more Smart Citations
“…The PETase-specific DS1, on the other hand, is located adjacent to the active site and connects the b7-a5 and b8-a6 loops that harbor the catalytic acid (D177) and catalytic base (H208), respectively (Fig. Interestingly, PET hydrolysis measured under reducing conditions and mutagenesis experiments indicate that DS1 depletion significantly reduces enzyme activity, suggesting that DS1 plays a critical role in PETase activity [9,[11][12][13]. In addition, the b8-a6 loop in PETase is three residues longer than that of other homologous enzymes (Fig.…”
Section: Unique Structural Features Of Petasementioning
confidence: 99%
“…Significantly, I. sakaiensis secretes a unique cutinase-like enzyme, later dubbed PETase, to hydrolyze PET to bis(2-hydroxylethyl) TPA (BHET), mono(2-hydroxyethyl) TPA (MHET), and TPA ( Fig. Here, we summarize the most recent studies of crystal structures of PETase and its complex with substrate/product analogs reported by ourselves and other groups [9][10][11][12][13]. Under physiological conditions (30°C, pH 7.0), the enzyme is 5.5-to 120-fold more efficient than previously reported PET-hydrolyzing homologs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ChemSusChem 2018, 11,4018 -4025 www.chemsuschem.org Low-crystalline PET hydrolysis unders tandard reaction conditions Standard reaction conditions were determined based on our previous report. [18] As control experiments, the same volume of buffer with the enzyme solution was added to the preincubated film and incubated for 3h.T he reaction was terminated after each incubation time by adding dilution solution (500 mL, 70 %v/v MilliQ, 20 %v/v acetonitrile, and 10 %v/v formic acid). The PET hydrolysis reaction was initiated by adding PETase (final concentration 500 nm)a t3 0 8C.…”
Section: Pet Film Preparationmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] For example, cutinases from Thermobifida fusca [8,9] and the most efficient PET hydrolyzing esterase, leaf and branch compost cutinase( LCC). [12][13][14][15][16][17][18][19][20] Although PETase is highly specific to PET,t he enzymes hows poor catalytic activity and is difficult to use in industrial processes. [12][13][14][15][16][17][18][19][20] Although PETase is highly specific to PET,t he enzymes hows poor catalytic activity and is difficult to use in industrial processes.…”
Section: Introductionmentioning
confidence: 99%